Pb1-x Cax TiO3 solid solution (x=0.0, 0.25, 0.50, and 0.75): A theoretical and experimental approach - De Lázaro, Sérgio Ricardo; De Lucena, Poty Rodrigues; Sambrano, Júlio Ricardo [UNESP]; Pizani, Paulo Sérgio; Beltrán, Armando; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (American Physical Society (APS), 2007)
In this paper we report an experimental and theoretical study based on a periodic density functional investigation into selected compositions of Pb1-x Cax TiO3 (x=0.0, 0.25, 0.50, and 0.75). Based on our findings, we propose that the pseudocubic structure of these perovskites presents a long-range tendency for cubic symmetry, while the short-range displacements bring the solid solution to a tetragonal symmetry. The results are discussed in terms of x-ray diffraction, structural optimized parameters, Raman spectroscopy, band structure, density of states, Mulliken charge, and overlap population. © 2007 The American Physical Society.